2013
DOI: 10.1111/j.1467-9817.2013.01555.x
|View full text |Cite
|
Sign up to set email alerts
|

Reading difficulties and attention‐deficit/hyperactivity behaviours: evidence of an early association in a nonclinical sample

Abstract: Attention-deficit/hyperactivity disorder (ADHD) often co-occurs with reading disability. A cross-sectional study in an Italian-speaking, nonclinical sample was conducted in an attempt to document the existence of an early association between reading difficulties (RD) and ADHD behaviours. We recruited a sample of 369 children in their first year at primary school. Of the sample, 8.4% displayed RD; 7.0% had ADHD; 3.5% presented both RD and ADHD behaviours; 50% of the children with ADHD displayed RD; 41.9% of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…This study revealed the role of the different components of attention on reading acquisition; other recent findings showed that disruption of attentional mechanisms plays a causal role in reading disability (e.g., Luoni et al., 2015; Shaywitz & Shaywitz, 2008). For this reason, the early assessment of attention might contribute to reducing reading difficulties when children begin primary school.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This study revealed the role of the different components of attention on reading acquisition; other recent findings showed that disruption of attentional mechanisms plays a causal role in reading disability (e.g., Luoni et al., 2015; Shaywitz & Shaywitz, 2008). For this reason, the early assessment of attention might contribute to reducing reading difficulties when children begin primary school.…”
Section: Resultssupporting
confidence: 66%
“…Research showed that children who spoke languages with opaque orthographies, such as English, acquired reading more slowly compared with their peers speaking transparent languages, such as Italian (Defior, 2004;Seymour, Aro, & Erskine, 2003). In this regard, Luoni et al (2015) suggested that learning to read requires a higher engagement of attention in opaque orthographies than transparent orthographies. This high involvement of attention could explain the comorbidity between reading disability and attentional disorders in populations whose language has opaque orthography, even if there are no data supporting this hypothesis.…”
Section: Why Attention Influences Reading Acquisitionmentioning
confidence: 99%
“…However, to our knowledge, the only meta-analysis to date of reading interventions for children with ADHD in special education settings revealed positive effects but found no use of evidence-based practices and was limited to a total of 65 participants across 16 studies. 36 Considering the comorbidity of word reading disabilities and attention deficits is estimated to be between 25% and 50% of children with reading difficulties, 37 , 38 it is important to look at attention struggles as a predictor of response to reading intervention.…”
Section: Introductionmentioning
confidence: 99%